Design of an Automated Capillary Electrophoresis Platform for Single-Cell Analysis - Abraham, David H. (Methods Enzymol, 2019)
Single-cell analysis of cellular contents by highly sensitive analytical instruments is known as chemical cytometry. A chemical cytometer typically samples one cell at a time, quantifies the cellular contents of interest, and then processes and reports that data. Automation adds the potential to perform this entire sequence of events with minimal intervention, increasing throughput and repeatability. In this chapter, we discuss the design considerations for an automated capillary electrophoresis-based instrument for assay of enzymatic activity within single cells. We describe the key requirements of the microscope base and capillary electrophoresis platforms. We also provide detailed protocols and schematic designs of our cell isolation, lysis, sampling, and detection strategies. Additionally, we describe our signal processing and instrument automation workflows. The described automated system has demonstrated single-cell throughput at rates above 100 cells/hour and analyte limits of detection as low as 10(−20) mol.